Dialectics of Text and Reality: Interpretation of the Verses of the Qur’an on Husband and Wife Relations from the Perspective of NU and Muhammadiyah theologians in the Cities of Salatiga and Surakarta - Mubasirun; Muhammad Irfan Helmy; Imam Sutomo (Millati: Journal of Islamic Studies and Humanities, 2025)
The fact that in society there are married women who work and have careers outside the home, raises debates in the interpretation of verses related to husband-wife relations. The purpose of this research is to reveal how NU and Muhammadiyah theologians interpret verses about husband-wife relations and the factors that influence these interpretations. The approach used in this research is a normative-sociological approach to highlight the views and ideas of NU and Muhammadiyah theologians about husband-wife relations. The use of a normative approach is to examine husband-wife relations in the verses of the Qur’an about husband-wife relations. Meanwhile, the sociological approach is used to see the views of theologians from Nahdlatul Ulama (NU) and Muhammadiyah circles about husband-wife relations as an interpretation of the verses of the Qur’an about husband-wife relations. For the purposes of analysis, the theory of Sociology of interpretation is used which refers to the view of Peter L Berger who states that the reality and knowledge that a person obtains are not given for free but are a dialect process between that person and the social reality that surrounds him which is then constructed into a text (interpretation). The research found that the interpretation of the NU and Muhammadiyah theologians of Salatiga and Surakarta regarding the shurah an-Nisa’[4];34 and al-Ahzab [33];33 did not have a problem with wives working and having careers outside the home as long as they obtained permission from their husbands.